Source, distribution, and risk assessment of polycyclic aromatic hydrocarbons in sediment and fish samples from River Owan, Edo State, Nigeria - Akinnusotu, Akinyinka; Ukpebor, Justina E.; Okieimen, Felix E. (Frontiers in Toxicology, 2023)
Polycyclic aromatic hydrocarbons (PAHs) are persistent environmental contaminants that present several environmental risks including human health. The 16 priority PAHs including its 1methylnaphthalene, and 2-methylnaphthalene were determined in sediment and fish samples (Clarias anguillaris and Oreochromis niloticus) of River Owan, Edo State, Nigeria using gas chromatography (GC) equipped with flame ionization detector (FID) and other standard laboratory protocols. The isomeric ratio was used for source diagnosis, sediment quality guidelines, and risk models of incremental lifetime cancer were used for risk assessment. 1-methylnaphthalene and 2methylnaphthalene were most predominant in all sediment samples analysed. The ∑LMW PAHs ranged between 0.093 -0.250 µg/kg; ∑HMW PAHs were 0.107 -0.579 µg/kg. The sediment samples range for ∑PAHs was 0.280 -0.810 µg/kg with concentration order of increase: SE5>SE4>SE3>SE6>SE1>SE2>SE7 for the seven sampling locations. The ∑PAHs for Oreochromis niloticus was 0.190 µg/kg, which is higher than the value of Clarias anguillaris 0.080 µg/kg, and these values were greatly lesser when compared to the European Commission limit of 12.00 µg/kg. The diagnostic ratio indicates that the sources are more pyrogenic than petrogenic, revealing combustion from grass, wood, and bush burning. Sediment quality assessment showed that the ∑PAHs were lower than the regulatory values of sediment quality guidelines (SQG) assessment suggesting no ecotoxicological effects on the benthic organisms in this area at present. The ILCR results were in the range of 9.15 x 10 -12 -1.46 x 10 -6 for children,